Vertical price coordination and brand care : interdisciplinary perspectives on the prohibition of resale price maintenance - Ahlert, Dieter (SpringerBriefs in Business, 2013)
Competition law regulates anti-competitive conduct by companies in order to maintain market competition. Cartel law can also cause restraints of competition and therefore, the existing regulations should be checked, revised and updated regularly. This book deals with the prohibition of Resale Price Maintenance, which is intensively discussed in Germany at the moment. It provides a new interdisciplinary approach to the topic that emphasizes the empirically observable marketing perspective, but draws conclusions from competition theory. Thus it reflects on the consumer benefits and welfare effects of RPM legalization at the same time. Since it provides new and constructive class-based suggestions for a re-design of European cartel law, this book should be valuable for researchers, practitioners and politicians.